'Truth in Fiction' Reprised. (4th June 2022) - García-Carpintero, Manuel
Abstract: The paper surveys recent appraisals of David Lewis's seminal paper on truth in fiction. It examines variations on standard criticisms of Lewis's account, aiming to show that, if developed as Lewis suggests in his 1983 Postscript A, his proposals on the topic are—as Hanley puts it—' as good as it gets '. Thus elaborated, Lewis's account can resist the objections, and it offers a better picture of fictional discourse than recent resurrections of other classic works of the 1970s by Kripke, van Inwagen and Searle. The turn that Lewis suggests and the paper recommends draws on the remaining outstanding contribution from that time: Walton's.